Diagnostic value comparison of CellDetect, fluorescent in situ hybridization (FISH), and cytology in urothelial carcinoma - Shang, Donghao; Liu, Yuting; Xu, Xiuhong; Chen, Zhenghao; Wang, Daye (Cancer cell international, 2021)
Background To evaluate the clinical effectiveness of a novel CellDetect staining technique, compared with fluorescent in situ hybridization (FISH), and urine cytology, in the diagnosis of urothelial carcinoma (UC). Methods A total of 264 patients with suspicious UC were enrolled in this study. All tissue specimens were collected by biopsy or surgery. Urine specimen was obtained for examinations prior to the surgical procedure. CellDetect staining was carried out with CellDetect kit, and FISH was performed with UroVysion detection kit, according to the manufacturer’s instructions. For urine cytology, all specimens were centrifuged using the cytospin method, and the slides were stained by standard Papanicolaou stain. Results In this study, there were 128 cases of UC and 136 cases of non-UC, with no significant difference in gender and age between the two groups. Results for sensitivity of CellDetect, FISH, and urine cytology were 82.8%, 83.6%, and 39.8%, respectively. The specificity of the three techniques were 88.2%, 90.4%, and 86.0%, respectively. The sensitivity of CellDetect and FISH are significantly superior compared to the conventional urine cytology; however, there was no significant difference in specificity among three staining techniques. In addition, the sensitivity of CellDetect in lower urinary tract UC, upper urinary tract UC, non-muscle-invasive bladder cancer (NMIBC), and muscle-invasive bladder cancer (MIBC) were 83.3%, 81.8%, 83.5%, and 72.0%, respectively. The screening ability of CellDetect has no correlation with tumor location and the tumor stage. The sensitivity of CellDetect in low-grade UC and high-grade UC were 51.6 and 92.8%. Thus, screening ability of CellDetect in high-grade UC is significantly superior compared to that in low-grade UC. Conclusions CellDetect and FISH show equal value in diagnosing UC, both are superior to conventional urine cytology. Compared to FISH, CellDetect is cost effective, easy to operate, with extensive clinical application value to monitor recurrence of UC, and to screen indetectable UC.